Monosaccharides modulate HCV E2 protein-derived peptide biological properties (2007)
A hepatitis C virus E2 protein-derived sequence was selected for studying the effect of N-glycosylation on the peptide chain’s conformational structure. The results suggested that the 534TDVF537 motif contained in peptide 33402 (529WGENDTDVFVLNNTRY544) had a type III ?-turn, relevant in antigen recognition of polyclonal antibodies, binding to human cells, and binding to HLA DRB1?0401 molecules. N-Glycopeptides derived from this sequence contained monosaccharides in Asn532. N-Glycopeptides presented differences in peptide chain structure compared to non-glycosylated peptides. Peptide 33402 specifically bound to human cells, specificity becoming lost when it was N-glycosylated. N-Glycosylation decreased antigen recognition of mouse polyclonal sera against this sequence. N-Glycopeptide binding to HLA DRB1?0401 molecules was similar to that presented by non-glycosylated peptide, indicating that N-glycosylation did not affect binding to HLA DRB1?0401 molecules. N-Glycosylation induced changes at structural and functional level which could be relevant for modulating human cell binding properties and antibody recognition.